The role of local estrogen therapy in the management of pelvic floor disorders. (3rd March 2016) - Tzur, T.; Yohai, D.; Weintraub, A. Y.
Abstract: Pelvic floor disorders are common and bothersome problems that include a variety of conditions. These conditions greatly affect the performance of daily activities and social function such as work, traveling, physical exercise, sleep and sexual function. Aging is a well-known factor affecting the pelvic floor and lower urinary tract anatomy and function. It is clear that the pelvic organs and their surrounding muscular and connective tissue support are estrogen-responsive. Treatment of pelvic floor disorders requires significant health-care resources and their impact is likely to increase in the near future. This literature review aims to provide an overview of both research and clinical aspects of the pathophysiology of urogenital estrogen deficiency and the role of local estrogen therapy as part of the management strategy of different pelvic floor disorders. The safety and risk concerns regarding the use of local estrogen therapy are addressed as well.